A flexible low insertion‐loss wideband millimeter‐wave crossover based on ridge gap waveguide technology. Issue 6 (7th March 2022) - Wang, Jie; Wu, Yongle; Yang, Yuhao; Wang, Weimin
Abstract: This paper presents a flexible low insertion‐loss wideband millimeter‐wave crossover based on the ridge gap waveguide (RGW) technology. Based on the design of periodic metal pins of gap waveguide (GW), the transmission modes in the ridge have been analyzed in detail. The influence of different widths of the ridge on the cutoff frequency of the quasi‐TEM mode and the first high‐order mode in GW are mainly discussed. According to the results of the mode analysis, a flexible wideband low insertion‐loss central‐crossover covering 42–51 GHz is designed, which can be easily used to form the Butler Matrix (BM). Furthermore, a transition from standard rectangular waveguide to RGW has been designed. Finally, to validate the proposed design method, a complete crossover prototype based on RGW technology operating from 42 to 45.5 GHz in U‐band is designed and fabricated. The measured results have a good agreement with simulated results.